Teenage Motherhood and its Effect on the Social Welfare of The Victims: A Case Study of Kabale Municipality. - Kwesiga, Siifa (Kabale University, 2024)
Teenagers in Uganda are increasingly starting sexual intercourse at early ages in their lives. Hence the study offers an in-depth analysis of the relative contribution of some socio¬demographic factors in explaining adolescent pregnancy in Kabale Municipality. Using primary data collected from different parts of the district, a sample of 30 female adolescents in the age range of 10-19 years was studied. Results from the study indicated that the level of education, sex, and age had a significant impact on the dependent variable (Teenage pregnancy). Some of the risk factors that were likely to cause teenagers to have unwanted pregnancies were; poor economic status, print media, lack of privacy, marriage before 18 years, and lack of sex education and counseling against pregnancy. Findings show teenage mothers were motivated by social support networks; social support was a motivating factor to carry on with the pregnancy and child raising. The study therefore recommends effective programs for teenagers with their involvement. There is great benefit in strengthening their knowledge and skills through sex education. Greater efforts are essential in dealing with their special needs and appropriate services should be made available.